The Ubiquitin Proteasome System and Nutrient Stress Response - Mackinnon, Erin; Stone, Sophia L. (Frontiers in Plant Science, 2022)
Plants utilize a variety of molecular mechanisms, including the ubiquitin proteasome system (UPS) that facilitate changes to the proteome, to mitigate the negative impact of abiotic stresses on growth and development. The UPS encompasses the ubiquitination of a selected substrate followed by the proteasomal degradation of the modified protein. Ubiquitin ligases, or E3s, are central to the UPS as they govern specificity, mediating the attachment of one or more ubiquitin molecules to the substrate protein. From recent studies, the UPS has emerged as an important regulator of the uptake and translocation of essential macronutrients and micronutrients. In this review, we discuss select E3s that are involved in regulating responses to nutrient stress, including limited or excess levels of nitrogen, phosphorus, iron, and copper.